Functional crosstalk across IMD and Toll pathways: insight into the evolution of incomplete immune cascades. Issue 1897 (20th February 2019) - Nishide, Yudai; Kageyama, Daisuke; Yokoi, Kakeru; Jouraku, Akiya; Tanaka, Hiromitsu; Futahashi, Ryo; Fukatsu, Takema
Abstract : In insects, antimicrobial humoral immunity is governed by two distinct gene cascades, IMD pathway mainly targeting Gram-negative bacteria and Toll pathway preferentially targeting Gram-positive bacteria, which are widely conserved among diverse metazoans. However, recent genomic studies uncovered that IMD pathway is exceptionally absent in some hemipteran lineages like aphids and assassin bugs. How the apparently incomplete immune pathways have evolved with functionality is of interest. Here we report the discovery that, in the hemipteran stinkbug Plautia stali, both IMD and Toll pathways are present but their functional differentiation is blurred. Injection of Gram-negative bacteria and Gram-positive bacteria upregulated effector genes of both pathways. Notably, RNAi experiments unveiled significant functional permeation and crosstalk between IMD and Toll pathways: RNAi of IMD pathway genes suppressed upregulation of effector molecules of both pathways, where the suppression was more remarkable for IMD effectors; and RNAi of Toll pathway genes reduced upregulation of effector molecules of both pathways, where the suppression was more conspicuous for Toll effectors. These results suggest the possibility that, in hemipterans and other arthropods, IMD and Toll pathways are intertwined to target wider and overlapping arrays of microbes, which might have predisposed and facilitated the evolution of incomplete immune pathways.